Outil décisionnel pour la mise en oeuvre nationale du système multilatéral d’accès et de partage des avantages aux termes du Traité international sur les ressources phytogénétiques pour l’alimentation et l’agriculture - Joint Capacity Building Programme (Bioversity International, 2018)
This decision making tool is designed to assist national policy makers and other stakeholders to identify appropriate measures to implement the Plant Treaty’s multilateral system of access and benefit-sharing in their countries.